Freedom of the Press On Censorship, Self-censorship, and Press Ethics - Dosenrode, Søren (Nomos Verlagsgesellschaft mbH & Co. KG, 2010)
Since antiquity it has been known that without the freedom to speak, and later to publish, the road to fanaticism and totalitarianism lies wide open. This book focuses on how the 'press' reacted, when press freedom was under strain in number of cases in the 20th century and the beginning of the 21st century. Contemporary literature on the freedom of the press has its focus on the role of the press in relation to democracy; how media influences democracy, how the political and the ethical aspects are managed etc. This book is on the one hand part of this central discourse. On the other hand, it attempts to broaden views by focusing on the historical and contemporary experiences, when press freedom was under strain in significant periods since the 1930s. Also, its geographical scope is broader than most books, and it brings together experienced journalists and known academics adding to the dynamism of the discussion and challenging the reader to find his own position concerning censorship, self-censorship and press ethics.